Chronic diseases and self-assessment of health as predictors of unmet health needs of the elderly population in the Republic of Serbia: national health survey - Savić, Nikola; Sovilj, Saša; Grbić, Gordana; Arnaut, Aleksandra; Jovanović, Verica; Kocić, Sanja (Vojnosanitetski pregled, 2024)
Introduction/Aim. Unmet health needs are the difference between the health services considered necessary to solve a particular health problem and the health services that were actually received. Unmet health needs in the elderly population with chronic diseases can lead to deterioration of the health condition and complications. The aim of the study was to analyze the connection between the presence of chronic diseases and self-assessment of health with the unmet health needs of the elderly population. Methods. The study was part of the latest National Population Health Survey of the Republic of Serbia, conducted as a cross-sectional study on a representative stratified two-stage sample. Data from 3,450 respondents aged 65 and above were used for the purposes of the research. The research was conducted according to the European population health research methodology. Univariate and multivariate logistic regression were used to assess predictors of unmet health needs. Results. Every third respondent with a chronic disease did not receive the necessary form of health care (36.3%). Dominant predictors of unmet health needs were self-assessment of health [odds ratio (OR) = 0.63; 95% confidence interval (CI) = 0.58–0.68] along with chronic diseases (OR = 2.29; 95% CI = 1.87–2.81) and depression (OR = 2.12; 95% CI = 1.71–2.64). Respondents with a chronic health disorder were 2.2 times more likely to fail in the realization of the necessary health service compared to respondents who did not have long-term illnesses. Respondents who assess their own health as poor/very poor report unfulfilled health needs two times more often than respondents in good health. Conclusion. Unmet health needs in the elderly population are associated with self-reported health and the presence of chronic diseases. The results of such research can be the basis for a better organization of health care and the creation of health policies in order to improve the health of this population group.